FABRIKASI FERROGEL BERBAHAN DASAR NANOPARTIKEL MAGNETIT (Fe3O4) DARI HASIL SINTESIS PASIR BESI PANTAI UTARA JAWA DAN SIFAT - Retno Rahmawati; Nita Handayani (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
Iron sand is one of natural materials that has been widely explored and so far is only used as building materials. This research provides solutions to increase the economic values of iron sand, by preparing ferrogel from iron sand. The purpose of this research is to prepare Fe3O4 nanoparticles-based-ferrogel from synthetic Fe3O4 prepared from iron sand. The iron sand was obtained from north coast of Central Java. The preparation of synthetic Fe3O4 produced nanoparticles having a size of 82,42 – 110,9 nm. The characterization using XRD indicated that Fe2O4 content in the iron sand was 30%, and increased to 76% in the synthetic materials. In addition, the synthetic materials has additional phase of Al0.95 Ga0.05. The ferrogel was prepared by mixing the synthetic materials with PVA (Polyphinyl alcohol). The ferrogel was characterized for its magnetoelasticity properties so that it can be used for artificial muscles. The results of magneto- elasticity ferrogel characterization showed that the higher the concentration of Fe3O4 filler in PVA matrix, the higher the deviation and elongation. However, the impurity of Al0.95 Ga0.05 in the ferrogel seemed to cause its magnetoelasticity to be less than optimum.